Investigating challenges and opportunities of applying block-chain technology to reduce agrifood loss - Habiba Elrouby; Sahar Elbarky; Amal Sakr (International Business Logistics Journal)
Purpose: Agriculture plays a significant role in the Egyptian economy, accounting for 11.3 percent of the nation's gross domestic product. The agricultural industry constitutes 28 percent of the workforce, with agriculture-related employment in Upper Egypt surpassing 55 percent. However, there are many challenges facing the Egyptian agrifood sector as poor post-harvest infrastructure, exposure to high temperatures, and poor handling practices. Moreover, In response to these challenges, this research aims to investigate the prospective challenges and opportunities of applying blockchain to reduce food waste, improve agri-food security and enhance food supply chain traceability in the Egyptian agri-Food industry. The methodologies employed in this study were instrumental in achieving the study objectives, which were twofold: (1) To identify the main challenges and factors that influence the adoption of blockchain technology in the agri-food industry, drawing on existing literature, and (2) To determine the relative significance of potential barriers that may arise during the implementation of blockchain technology in the Egyptian agrifood sector. Design Methodology/Approach: The investigation was conducted using a quantitative research design, first tracing the literature to identify issues related to the adoption of blockchain technology in the agri-food industry. Additionally, a questionnaire-based methodology was used to gather data. The sample consisted of 37 participants, who were conveniently picked from seven agricultural organizations in Egypt.   Findings: The findings give a full comprehension of the obstacles associated with the use of blockchain technology in the Egyptian agrifood industry which are “Scalability”, “lack of trust among users”, “lack of workforce expertise”, and “lack of Egyptian regulations governing blockchain technology adoption”. while the potential opportunities are agrifood supply chain “traceability”, “cooperation”, and “efficiency”. These findings provide a valuable contribution to enhancing management decision-making and digital strategies pertaining to the adoption of blockchain technology inside firms, as well as providing insights into efficient implementation tactics. Research Implications/Limitations: This study contributes to the existing body of literature by exploring the potential of blockchain technology in improving agri-food security and mitigating agrifood loss in Egypt as a developing country. However, there is a noticeable lack of scholarly study about the use of Blockchain technology in developing countries. Also, blockchain technology still has some challenges and limits that need to be resolved. This calls for more research and study.   Practical Implications/Limitations: The findings of this study may provide agri-food managers, blockchain technology service providers, and governmental entities with useful insights that can be used in the development of effective strategies and regulations for the successful application of blockchain technologies within the Egyptian agrifood sector, with the end goal of reducing agrifood loss. However, this has yet to be proven and is just limited to the literature.   Originality: The current food security issue in Egypt presents a significant risk to the country's economy. The precarious condition of Egypt's food security arises from the agricultural sector's insufficient capacity to adequately provide cereal grains, particularly wheat, and oilseeds, hence failing to satisfy even half of the nation's internal requirements. Moreover, Egypt depends on significant quantities of highly subsidized imports in order to guarantee an adequate and cheap supply of bread and vegetable oil for its population of 105 million individuals. There are several factors contributing to agri-food scarcity, one of which is food loss resulting from inefficient harvesting procedures and insufficient post-harvest management practices. Accordingly, this study presents an analysis of the potential challenges and opportunities associated with the use of blockchain technology in the agri-food sector of Egypt aiming to reduce agrifood loss and enhance food security. Additionally, this study is the first of its kind to comprehensively examine the barriers and facilitators of blockchain adoption in Egypt.   Received: 14 August 2023 Accepted: 15 October 2023 Published: 15 December 2023